Re-sensitising the body: interactive art and the Feldenkrais method. (1st January 2013) - Loke, Lian; Khut, George Poonkhin; Slattery, Maggie; Truman, Catherine; Muller, Lizzie; Duckworth, Jonathan
This article describes interdisciplinary research undertaken by a group of artists, designers, curators and somatic bodywork practitioners to explore a human-centred approach to the potential of touch, movement, balance and proprioception as modalities for interactive art. Somatic bodywork methodologies such as the Feldenkrais method provide highly developed frameworks for attending to these very phenomena. Re-sensitising the body through somatic investigations allowed us as makers of body-focussed interactive art to translate the subtle shifts in attention and nuances of felt sensation into the audience experience of sensor-based interactive artworks. We describe the results of a yearlong project through our experience of the making of one specific experimental artwork, surging verticality. We reflect on the conditions for audience engagement and the profound connections we experienced between Feldenkrais somatic bodywork and art practice as modes of enquiry into the world.